Post-extraction implant rehabilitation; clinical case report - Chiluisa Muso, Rosa Ana (2019)
In the implant rehabilitations supported in the previous sector, a surgical and prosthetic protocol should be carried out as a mechanism to ensure the aesthetics and function of the procedure to be performed. The objective of this clinical case is to present a rehabilitation protocol in a soft tissue test and management document to preserve aesthetics through provisional prosthetic structures, ending with rehabilitation with the zirconium oxide abutment with titanium base and a crown of lithium disilicate as means to achieve high aesthetics. The prediction of a unitary implant in the anterior sector requires the clinician to know three-dimensional structures conjugated with a soft tissue and material handling in an appropriate way, to predict the medium- or long-term behavior in the protection and prevention of aesthetics.